2021
DOI: 10.3389/fcell.2021.647717
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Transcriptomic Analysis of Spermatozoa From High- and Low-Fertile Crossbred Bulls: Implications for Fertility Prediction

Abstract: Crossbred bulls produced by crossing Bos taurus and Bos indicus suffer with high incidence of infertility/subfertility problems; however, the etiology remains poorly understood. The uncertain predictability and the inability of semen evaluation techniques to maintain constant correlation with fertility demand for alternate methods for bull fertility prediction. Therefore, in this study, the global differential gene expression between high- and low-fertile crossbred bull sperm was assessed using a high-throughp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(24 citation statements)
references
References 93 publications
0
22
0
2
Order By: Relevance
“…Post-chilled sperm characteristics of crossbred spermatozoa by next generation RNA Sequencing revealed the transcripts for 13,814 genes, which are highly related to ribosome, spliceosome and oxidative phosphorylation pathways (Prakash et al, 2020(Prakash et al, , 2021, whereas microarray analysis revealed the expression of 19,454 genes in Vrindavani crossbred bull sperm (Yathish et al, 2017). The PRM1 is an abundant transcript found in spermatozoa of crossbred bulls (Singh et al, 2019;Prakash et al, 2020), which is also abundant in Bos indicus (Raval et al, 2019) and Bos taurus (Card et al, 2013;Selvaraju et al, 2017) bulls.…”
Section: Seminal Parameters Purebred Bulls Crossbred Bullsmentioning
confidence: 99%
See 2 more Smart Citations
“…Post-chilled sperm characteristics of crossbred spermatozoa by next generation RNA Sequencing revealed the transcripts for 13,814 genes, which are highly related to ribosome, spliceosome and oxidative phosphorylation pathways (Prakash et al, 2020(Prakash et al, , 2021, whereas microarray analysis revealed the expression of 19,454 genes in Vrindavani crossbred bull sperm (Yathish et al, 2017). The PRM1 is an abundant transcript found in spermatozoa of crossbred bulls (Singh et al, 2019;Prakash et al, 2020), which is also abundant in Bos indicus (Raval et al, 2019) and Bos taurus (Card et al, 2013;Selvaraju et al, 2017) bulls.…”
Section: Seminal Parameters Purebred Bulls Crossbred Bullsmentioning
confidence: 99%
“…When two different species or breeds are crossed to produce hybrid offspring, the compatibility between spermatozoon and oocyte is altered ( Jodar et al, 2013 ); this compatibility is essential for the transfer of RNA-based information to a chromatized state (Consolidation process). Global transcriptomic profiling of crossbred spermatozoa by next generation RNA Sequencing revealed the transcripts for 13,814 genes, which are highly related to ribosome, spliceosome and oxidative phosphorylation pathways ( Prakash et al, 2020 , 2021 ), whereas microarray analysis revealed the expression of 19,454 genes in Vrindavani crossbred bull sperm ( Yathish et al, 2017 ). The PRM1 is an abundant transcript found in spermatozoa of crossbred bulls ( Singh et al, 2019 ; Prakash et al, 2020 ), which is also abundant in Bos indicus ( Raval et al, 2019 ) and Bos taurus ( Card et al, 2013 ; Selvaraju et al, 2017 ) bulls.…”
Section: Compounding Factors For Infertility/sub-fertility In Crossbred Bullsmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, they may have an association with potentiated DNAs for gene expression ( Jodar et al, 2013 ). Further, the sperm transcriptome profiling using Microarray ( Das et al, 2013 ; Zhang Y. et al, 2017 ), and RNA-seq ( Gòdia et al, 2018 ) have identified a suite of RNAs in spermatozoa ( Sendler et al, 2013 ) that included both coding and non-coding transcripts and were associated with regulation of various biological functions such as chromatin repackaging, genomic imprinting, early embryonic development ( Das et al, 2013 ), and post-fertilization events ( Prakash et al, 2021 ). The spRNA profile also differed between low-motile and high-motile spermatozoa ( Lambard et al, 2004 ) and between fertile and infertile men ( Wang et al, 2004 ; Ostermeier et al, 2005 ).…”
Section: Introductionmentioning
confidence: 99%
“…Altered miRNAs expression has also been found in the testis with non-obstructive azoospermia ( Lian et al, 2009 ). Thus, the expression level of spRNAs and seminal RNAs may have potential use in studying the post-spermatogenesis events and detecting defects in sperm function ( Prakash et al, 2021 ). A layout of whole transcriptome studies in major livestock species is presented in Figure 1 .…”
Section: Introductionmentioning
confidence: 99%